2003
DOI: 10.1103/physreva.67.053401
|View full text |Cite
|
Sign up to set email alerts
|

Fast and efficient loading of a Rb magneto-optical trap using light-induced atomic desorption

Abstract: We have obtained fast loading of a rubidium magneto-optical trap and very high collection efficiency by\ud capturing the atoms desorbed by a light flash from a polydimethylsiloxane film deposited on the internal\ud surface of a cell. The atoms are trapped with an effective loading time of about 65 ms at a loading rate greater\ud than 23108 atoms per second. This rate is larger than the values reported in literature and is obtained by\ud preserving a long lifetime of the trapped atoms. This lifetime exceeds the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 18 publications
0
56
0
Order By: Relevance
“…It is noted that LIAD in vapor cells was first observed for silane coatings (in particular, polydimethylsiloxane) on cell walls in the early 90s [19], and since then there have been many investigations [20][21][22][23] including desorption from a paraffin coating [24]. In this paper we do not discuss LIAD from polymer coatings, because its mechanism is probably different from the desorption from bare glass surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that LIAD in vapor cells was first observed for silane coatings (in particular, polydimethylsiloxane) on cell walls in the early 90s [19], and since then there have been many investigations [20][21][22][23] including desorption from a paraffin coating [24]. In this paper we do not discuss LIAD from polymer coatings, because its mechanism is probably different from the desorption from bare glass surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most remarkable applications of LIAD is the efficient loading of Magneto-Optical Traps (MOTs) [63,64] and atom chips [65,66]. This technique gained a renewed attention after [2,37]: the possibility of controlling and quickly modulating the background vapor density, in fact, it permits obtaining large trapped populations during the loading phase, while maintaining good ultra-high vacuum conditions in the following stages, thus without compromising the lifetime of the cold atoms sample.…”
Section: Liad From Organic Coatings For Cold Atomsmentioning
confidence: 99%
“…Once the desired MOT population is reached, in order to prevent reduction of the trap lifetime due to background collisions, the desorbing source is switched off and the vacuum system re-establishes the initial vacuum conditions. Pulsed photo-desorption from PDMS coating deposited on the inner surface of a Pyrex vacuum chamber was applied to the loading of an 85 Rb MOT [64]. The abrupt burst of atoms released in the vapor phase allowed fast loading of the magneto-optical trap at a remarkable rate of 2 × 10 8 s −1 , without relevant consequences on the vacuum conditions and hence on the lifetime of the MOT.…”
Section: Liad From Organic Coatings For Cold Atomsmentioning
confidence: 99%
“…This reloading of the atom sources means that the total number of atoms in the device can be reduced through recycling. Studies have shown an order of magnitude improvement of MOT loading rates with this technique 83,84 , and it has been used to make BECs, which are very sensitive to background gas collisions, in a single chamber 85 . In chip-scale systems the surface area is far too small for effective use of LIAD 86 but, as mentioned earlier, one can introduce high surface area materials 87,88 providing they can be degassed sufficiently prior to encapsulation.…”
Section: Atom Source and Controlmentioning
confidence: 99%